The impact on regional "resource curse" by coal resource tax reform in China—A dynamic CGE appraisal. (September 2015) - Xu, Xiaoliang; Xu, Xuefen; Chen, Qian; Che, Ying
Abstract: The phenomenon of regional "resource curse" appeared gradually with the rapid development of Chinese economy. China with heavy energy consumption reliance on coal tried to get balance between economic stability and regional development by resource tax reform. In our dynamic computable general equilibrium model (CGE), the paper looked into the influences on economy, resource and environment with different coal resource tax policy scenarios from a regional perspective. The stimulated results showed coal resource tax reform had a negative influence on Gross Domestic Product (GDP). However, coal resource tax reform can increase regional revenues (especially in resource-rich regions) which helped to explain the exaltation of GDP in some regions, and seemed to be a highly potential way for narrowing regional economic gap. "Resource curse" regions reduction depended on resource tax rate which affected the supply and demand of elementary factors, and prevented human and capital resource crowded from the processing of the productions. And resource tax burden has alleviated as resource value subsidy for households and firms by using more alternative resources. Meanwhile, subsidy improved the quality of resource and environment. So we suggested that resource tax rate and subsidy should be taken into account in eliminating regional "resource curse" and coordinate resource and environment system within coal resource tax reform. Highlights: The paper looked into the influences on economy, resource and environment by coal resource tax reform from a regional perspective with different policy scenarios based on dynamic CGE model. Results showed that coal resource tax reform has a negative influence on GDP, but increase regional revenues and environment welfare."Resource curse" regions reduction and environment improvement depend on the quality of resource policy. We concluded resource tax rate and subsidy should be taken into account into the design of policy.